Woodrow Strong: capstone - Strong, Woodrow, artist (Colorado State University. Libraries, 2019)
The artist's statement: I have been told that I am a very private individual, that I look like I want to become invisible. This is not entirely true; I desperately want to be seen, and it is that impulse which drives me. I want others to know me, deeply and intimately, but on my terms. This can only be achieved through this broad self-portraiture, combining drawings and text in a way that creates a broader narrative of myself, and the things that make me who I am today. Within the work, the depictions of myself vary, because the way I feel about myself varies from day to day and moment to moment. In Self Conscious 1, I appear both masculine and feminine, clothed and unclothed, active and at rest, in color and in monochrome. An image of myself in sexual, feminine clothing appears in full color and reflects the vitality I feel when inhabiting that part of my identity. My hair changes shapes as I grapple with my gender identity within the work; the person I want to be, Holly, appears in contrast with the shorter-haired depictions of Woodrow. The desire to change my gender is a source of pain, a conflict waged entirely within my head; it is only through the work that this conflict becomes visible. Objects become incorporated into the work as well, objects that I've come to be identified with, or feel strongly about. My own art-making implements appear in Exploded Self Portrait, an x-acto knife and an eraser and an inkwell. There aren't as many objects as self portraits, though, because I do not generally use them to identify myself. They retain importance in my life, however, so excluding them entirely would have been dishonest. The text appears in speech bubbles in Exploded Self Portrait; though the work is nonlinear and each drawing is outwardly disconnected from the next, the text ties the entire work together into a single nonlinear narrative. I feel it wouldn't be disingenuous to call my work narrative self portraiture. In Self Conscious 1, the text occupies a far more prominent role. The text reveals things that I felt could not be conveyed through imagery, things I felt I needed to be said, or things that I felt within a single specific moment during my work on the piece. The text is direct, as honest and as authentic as I could make it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing